(untitled) (BioLaw Journal - Rivista di BioDiritto, 2026)
The contribution retraces four years of activity concerning requests for medical aid in dying in the Tuscany Region, before and after Regional Law 16/2025. In particular, it examines two emblematic cases, highlights unresolved issues, and puts forward proposals.